Economic Development in Different Regions in India Government of India, Planning Commission - Planning Commission (Planning Commission, 1962)
The object of this paper is to present a short factual account of development achieved during the ten years 1950-51 to 1960-61 and that projected during the Third Plan in different regions in India. For the purpose of this paper, Slates have been divided into five regions on the basis of Zones laid down in the States Reorganisation Act, 1956, except that the southern region is taken to include four Stales namely, Andhra Pradesh, Madras, Mysore and Kerala, and the western zone to include only two Slates, namely, Maharashtra and Gujarat. I. General Approach The population and area of each of the regions arc shown in Table in the Appendix.
Government of India, Planning Commission